Canon 626: Procurement of Votes in a Canonical Election - Austin, Brian T. ca. 20./21. Jh. (Roman Replies and CLSA Advisory Opinions 2021, 2021)
Does circulating lists of preferred candidates constitute procurement of votes? If so, how may information regarding more worthy and suitable candidates licitly be sought?